Heat transfer processes at the gas hydrate plug dissociation; International Journal of Heat and Mass Transfer; Vol. 256, pt. 1 - Podgornaya E. R. Elizaveta Romanovna; Nagibin P. S. Pavel Sergeevich; Shkola M. V. Mariya Valerjevna; Shlegel N. E. Nikita Evgenjevich; Strizhak P. A. Pavel Alexandrovich (2026, 2026)
Title screen